The Impact of Using ‘MagicSchool.ai’ as an Artificial Intelligence Platform to enhance Teachers’ ICT Self-Efficacy and Teaching Performance: The Case of EFL Teachers in Selmi Belgacem Middle School -Taoura- Souk Ahras - Omaima DJERIDI (My University, 2024)
ABSTRACT The integration of Information and Communication Technologies (ICT) in education remains challenging for many teachers due to limited technological skills, lack of confidence, and inadequate training. Scholars suggested Artificial Intelligence (AI) platforms, like MagicSchool.ai, which offer potential solutions to support teachers’ effective technology use. This study investigated the impact of MagicSchool.ai on middle school EFL teachers to enhance their ICT self-efficacy for instruction as well as their teaching performance. Two middle school EFL teachers from Selmi Belgacem Middle School -Taoura- participated in the study, in which we adopted a true experiment, classroom observations, and structured interviews. The findings revealed that using MagicSchool.ai significantly improved the participating teacher’s self-efficacy beliefs regarding effective ICT integration for instruction and she demonstrated notable enhancements in her overall instructional practices and teaching performance after utilizing the AI platform. Hence, this study provides empirical evidence on the potential use of MagicSchool.ai to enhance teachers’ ICT self-efficacy and teaching performance. ------------------ الملخص إن دمج تكنولوجيا المعلومات والاتصالات في التعليم يعتبر تحدياً للعديد من الأساتذة بسبب محدودية المهارات التكنولوجية، نقص الثقة، والتدريب غير الكافي. اقترح الباحثون منصات الذكاء الاصطناعي مثل MagicSchool.ai التي تقدم حلولاً لدعم الاستخدام الفعال للتكنولوجيا من قبل الأساتذة. تبحث هذه الدراسة في تأثير MagicSchool.ai على أساتذة اللغة الإنجليزية كلغة أجنبية في الطور المتوسط لتحسين كفاءتهم الذاتية في استخدام تكنولوجيا المعلومات والاتصالات في التعليم وكذلك أدائهم التدريسي. شارك في الدراسة معلمان من متوسطة سالمي بلقاسم - تاورة، حيث اعتمدنا على تجربة حقيقية، ملاحظات في الفصل الدراسي، ومقابلات منظمة. كشفت النتائج أن استخدام MagicSchool.ai حسّن بشكل كبير معتقدات الكفاءة الذاتية للأستاذة المشاركة في التجربة التي درّبتها على الدمج الفعال لتكنولوجيا المعلومات والاتصالات في التعليم وأظهرت تحسنا ملحوظا في ممارساتها التعليمية العامة وأدائها التدريسي بعد استخدام منصة الذكاء الاصطناعي. وبالتالي، قدّمت هذه الدراسة أدلة تجريبية على فعالية MagicSchool.ai لتعزيز كفاءة الأساتذة الذاتية في استخدام تكنولوجيا المعلومات والاتصالات وأدائهم التدريسي --------------------- mé L’intégration des technologies de l’information et de la communication (TIC) dans l’éducation reste un défi pour de nombreux enseignants en raison de compétences technologiques limitées, d’un manque de confiance et d’une formation inadéquate. Des chercheurs ont suggéré des plateformes d’Intelligence Artificielle (IA) comme MagicSchool.ai qui offrent des solutions potentielles pour soutenir une utilisation efficace des technologies par les enseignants. Cette étude examine l’impact de MagicSchool.ai sur des enseignants d’anglais comme une langue étrangère du CEM pour améliorer leur auto-efficacité en matière de TIC pour l’enseignement ainsi que leurs performances d’enseignement. Deux enseignants d’anglais de l’école moyenne Selmi Belgacem - Taoura - ont participé à l’étude, dans laquelle nous avons adopté une expérience réelle, des observations en classe et des entretiens structurés. Les résultats ont révélé que l’utilisation de MagicSchool.ai a considérablement amélioré les croyances d’auto-efficacité de l’enseignante de groupe expérimentale et elle a démontré des améliorations notables dans ses pratiques pédagogiques globales et ses performances d’enseignement après avoir utilisé la plateforme d’IA. Par conséquent, cette étude fournit des preuves empiriques sur l’utilisation potentielle de MagicSchool.ai pour améliorer l’auto-efficacité des enseignants en matière de TIC et leurs performances d’enseignement.